1994
DOI: 10.1159/000196311
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Exercise Capacity in Various Groups of HIV-lnfected Patients

Abstract: It is known that pulmonary function is impaired during the course of HIV infection even in early stages. In order to estimate the resulting reduction of exercise capacity, different groups of HIV patients were investigated. Group 1 consisted of 20 patients without a history of respiratory disease and without actual lung disease, group 2 of 18 patients with a former episode of Pneumocystis carinii pneumonia (PCP) without actual lung disease, and group III of 37 patients with different broncho-pulmonary complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 1 publication
3
26
0
3
Order By: Relevance
“…VeT is reduced in conditions characterized by excessive fatigue, including heart failure (12), chronic fatigue syndrome (33), chronic pulmonary disease (45), and acromegaly (60). In this study, VeT was significantly lower than that predicted for healthy sedentary males of similar age, body mass, and stature (18), confirming previous reports of reduced VeT in HIVinfected patients compared with healthy controls (31,47,53).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…VeT is reduced in conditions characterized by excessive fatigue, including heart failure (12), chronic fatigue syndrome (33), chronic pulmonary disease (45), and acromegaly (60). In this study, VeT was significantly lower than that predicted for healthy sedentary males of similar age, body mass, and stature (18), confirming previous reports of reduced VeT in HIVinfected patients compared with healthy controls (31,47,53).…”
Section: Discussionsupporting
confidence: 87%
“…Muscle wasting is associated with impaired strength and functional performance (24) and is alleged to be the underlying cause of increased fatigue among such patients. Additionally, diminished aerobic capacity in this patient population is well demonstrated by clinical exercise testing (14,31,32,36,46,47,53). Due to the strong association between HIV-associated muscle wasting and survival, as well as the concomitant diminutions of aerobic capacity and functional status, there has been considerable interest in targeted interventions.…”
mentioning
confidence: 99%
“…Oxygen utilization at peak exercise (VO2peak) is a gold standard for aerobic exercise capacity and is significantly impaired in HIV-infected adults [15], which is associated with increased age [13], hypertension [16], hyperlactatemia [17], and low CD4 cell count [18]. However, cardiorespiratory testing requires expensive equipment and specially trained staff.…”
Section: Introductionmentioning
confidence: 99%
“…Anaemia alone may account for the reduction in VO 2 max noted in some studies (Pothoff et al 1994, Stringer 2000.…”
Section: Anaemiamentioning
confidence: 87%
“…Alveolar arterial oxygen difference was also significantly greater during exercise in group 3. They concluded that HIV infection is associated with impairment of diffusing capacity and exercise capacity and questioned whether the problem was in oxygen delivery or muscle utilisation (Pothoff et al 1994).…”
Section: Exercise and Lung Functionmentioning
confidence: 99%